(untitled) (Malaysian Journal of Civil Engineering, 2018)
Self Compacting Concrete (SCC) is a concrete that is able to flow under its own weight and completely fill the formwork, even in the presence of congested reinforcement, without any compaction, while maintaining homogeneity of the concrete. The elimination of compaction for SCC is beneficial in solving difficult casting conditions and reduction in manpower required. SCC was added with relatively short, discrete, and discontinuous glass fibers to produce Glass Fiber Reinforced Self Compacting Concrete (GFRSCC). Water-cement (w/c) ratio of 0.40 was used in concrete mix proportions. The fiber used was alkaline-resistance glass fiber. Three volume percentages of fiber were added to the mix, i.e. 0.5%, 1.0%, and 1.5% by volume of concrete. Workability and mechanical properties of the concrete were evaluated. SCC and GFRSCC were highly workable than normal concrete (NC). The dosage of superplasticizer required increment as fiber content increase. SCC exhibits higher compressive strength than NC and GFRSCC. Inclusion of fibers does not give positive effect to the compressive strength of GFRSCC. The splitting tensile strength of NC was higher than SCC and GFRSCC due to the negative influence of superplasticizer added. Results indicated that the flexural strength of NC was slightly higher than SCC. The flexural strength of GFRSCC was higher than SCC. The optimum fiber content for GFRSCC, determined during the study was 1.0% by volume of concrete. GFRSCC slab developed higher first crack load and ultimate load compared to NC and SCC slabs